Quantitative relationships between elastic modulus of rod and biomechanical properties of transforaminal lumbar interbody fusion: a finite element analysis - Li, Jie; Du, Zengfeng; Cao, Shuai; Lu, Teng; Sun, Zhongwei; Wei, Hongyu; Li, Haopeng; Zhang, Ting (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundCurrently, some novel rods with lower elastic modulus have the potential as alternatives to traditional titanium alloy rods in lumbar fusion. However, how the elastic modulus of the rod (rod-E) influences the biomechanical performance of lumbar interbody fusion remains unclear. This study aimed to explore the quantitative relationships between rod-E and the biomechanical performance of transforaminal lumbar interbody fusion (TLIF).MethodsThe intact finite element model of L1-S1 was constructed and validated. Then 12 TLIF models with rods of different elastic moduli (ranging from 1 GPa to 110 GPa with an interval of 10 GPa) were developed. The range of motion (ROM) of the fixed segment, mean strain of the bone graft, and maximum von Mises stresses on the cage, endplate, and posterior fixation system models were calculated. Finally, regression analysis was performed to establish functional relationships between rod-E and these indexes.ResultsIncreasing rod-E decreased ROM of the fixed segment, mean strain of the bone grafts, and peak stresses on the cage and endplate, while increasing peak stress on the screw-rod system. When rod-E increased from 1 GPa to 10 GPa, ROM decreased by 10.4%–39.4%. Further increasing rod-E from 10 GPa to 110 GPa resulted in a 9.3%–17.4% reduction in ROM. The peak stresses on the posterior fixation system showed a nonlinear increase as the rod-E increased from 1 GPa to 110 GPa under most loading conditions. The R2 values for all fitting curves ranged from 0.76 to 1.00.ConclusionThe functional relationships between rod-E and the biomechanical properties of TLIF were constructed comprehensively. When the rod-E exceeds 10 GPa, further increases may not significantly improve stability, however, it may increase the risk of fixation failure. Therefore, a rod with an elastic modulus of approximately 10 GPa may provide optimal biomechanical properties for TLIF.